Risk factors for cerebrovascular disease. Bibliographic Review - Fernandez Rojas, Yoannia Caridad; Valido Valdes, Doraimys; Sánchez Rodríguez, Yanely; Gallardo Romero, Emma; Vilaú Suárez, Wilman Meylin (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Cerebrovascular disease (CVD) is currently one of the most important health problems, not only in Cuba, but also in developed countries. It is the second leading cause of death and permanent disability in adults worldwide. Objective: to provide updated information on the risk factors of cerebrovascular disease and its prevention from primary health care.Method: a search of the respective bibliography was performed in PubMed, Medline, Scielo and Google Scholar databases published during the period 2018- 2023, using the keywords: cerebrovascular disease, risk factors, diet, habits, mortality.Conclusions: The scientific literature identifies that disability and mortality generated by cerebrovascular disease represent important figures worldwide, it mainly impacts the population of older adults, with their multiple comorbidities and lifestyle habits, which in turn become important risk factors for presenting cerebrovascular disease.